Pedagogical vignettes of Chinese and Taiwanese folk songs suitable for late-elementary-upper intermediate level piano students - Hsu, Cheng-Jen (Kansas State University, 2014)
Folk songs are songs of unknown authorship passed down orally generation to generation, and often found in variants of words and tunes in different parts of a country or in different countries. They often represent the culture, the tradition, the life style and the music style in their era. Although there are many folk songs are still popular, they are rarely played during the piano lessons in Taiwan. In today’s piano lessons, the teaching mainly focuses on Western music and theory, like the major-minor system. The student begins to learn piano by the methods such as John Thompson or Nancy & Faber Piano Adventures. These methods build the foundation of their playing technique and the music theory. As their level goes up, they might have some opportunities to play the folk songs that are sung in different countries, such as the Hungarian folk music arranged by Bela Bartok. In the meantime, the piano teacher in Taiwan should not forget that they may have the responsibility to help the next generation to preserve the folk songs which present their culture. My research consists of an examination and performance of sixteen Chinese and Taiwanese folk songs in two collections: Piano Pieces on Chinese Folk Tunes for Children by Shui-Long Ma and Piano Pieces on Taiwanese Folk Tunes by Ching-Yi Lin. Each piece will be carefully graded into five levels: Elementary; Late Elementary/Early Intermediate; Intermediate; Upper-Intermediate; and Advanced. The features of each level will be discussed as well as the historical background and pedagogical aspects in particular piece of each level.
Keywords: Piano pedagogy; Chinese and Taiwanese folk songs; Music (0413)